High belite iron aluminate cement clinker and preparation method thereof
By introducing B, Ba and Cu elements into high-Belite iron aluminate cement, the crystal structure of the ore phase was changed, and the problems of steel bar corrosion and FRP steel mechanical properties degradation in seawater and sea sand concrete were solved, and a high-strength, high-corrosion-resistant seawater concrete structure was achieved.
Patent Information
- Application Number
- CN202510082137.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The use of seawater and sea sand concrete in marine engineering will cause steel bar corrosion and concrete cracking, thereby shortening the service life of the structure. At the same time, the mechanical properties of FRP ribs deteriorate in high alkaline environments and poor durability.
High Belite ferroalaluminate cement raw materials are used to change the crystal structure of the main mineral phases in cement clinker by introducing B, Ba and Cu elements, reduce the early hydration hardening rate, improve the later strength development, and mix and condense hardening in seawater.
The low alkalinity, high early strength and high corrosion resistance of the high Bellet ferroalaluminate cement system are achieved, and the problems of fast coagulation hardening in the early stage and slow strength development in the later stage are alleviated, and the mechanical strength is improved. It is suitable for FRP-enhanced seawater and sea sand concrete structures.
Smart Images

Figure BDA0005250716520000061 
Figure BDA0005250716520000071 
Figure BDA0005250716520000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a preparation method of high-belite ferroaluminate cement raw material, clinker and cement and clinker. Background Art
[0002] Under the background of the strategy of building a strong maritime nation, my country has gradually accelerated the construction of near and far sea infrastructure, resulting in a large demand for construction materials, aggravating the shortage of freshwater river sand construction resources in my country. Excessive exploitation will cause damage to the river ecological environment. However, my country has vast sea areas and a long coastline, rich reserves of seawater sand, and low mining difficulty. Using seawater sand instead of freshwater river sand for the construction of marine civil engineering infrastructure can alleviate the shortage of construction resources in my country and solve the problem of freshwater river sand supply difficulties in near and far sea engineering construction. However, the harsh service environment of marine engineering, coupled with the use of seawater sand concrete, will cause serious steel corrosion and concrete cracking problems, accelerating the damage and failure of reinforced concrete structures.
[0003] Fiber-reinforced composite material FRP bars have the characteristics of light weight, high strength and seawater corrosion resistance, and are ideal materials for replacing steel bars in seawater and sea sand concrete structures. However, the high alkaline environment in ordinary Portland cement concrete (pore solution pH value above 13) will cause the mechanical properties of FRP bars to deteriorate and the durability to deteriorate. In addition, in the harsh environment of high salt and high humidity in the ocean, concrete is invaded by corrosive ions such as sulfate, causing expansion damage, which is also one of the main reasons for the shortened service life of marine civil engineering structures.
[0004] Starting from the mineral composition of cement clinker, reducing the C3S and C3A content to form high belite cement can significantly reduce the alkalinity of the cementitious material hydration system and improve the salt erosion resistance, but it will cause difficulties in the early strength development and coagulation and hardening of concrete. On the basis of high belite cement, the introduction of early strength low-alkali mineral phase C4A3$ can regulate the coagulation and hardening time and strength development to form a high belite ferroaluminate cement system. Although high belite ferroaluminate cement has the performance characteristics of low alkalinity, high early strength and high corrosion resistance, it also has the disadvantages of fast coagulation and hardening and slow late strength development. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a method for preparing high-belite ferroaluminate cement raw material, clinker, cement and clinker. The high-belite ferroaluminate cement clinker prepared by using the raw material of the present invention not only has the performance characteristics of low alkalinity and high corrosion resistance, but also has a slowed early coagulation and hardening rate, a fast later strength development, and high mechanical strength, and is suitable for the purpose of FRP-reinforced seawater and sea sand concrete structures.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a high-belite ferroaluminate cement raw material, which comprises, by weight percentage, the following chemical compositions: CaCO3: 50-60%, SiO2: 10-13%, Al2O3: 15-20%, Fe2O3: 3-5%, CaSO4: 5-10%, B2O3: 1-1.5%, BaCO3: 5-8% and CuO: 0-0.5%.
[0008] The present invention provides a high-belite ferroaluminate cement clinker, which is obtained by calcining the high-belite ferroaluminate cement raw material described in the above scheme;
[0009] Based on the mass percentage of 100%, the mineral phase composition of the high-belite ferroaluminate cement clinker includes: orthorhombic C4A3$: 20-30%, cubic C4A3$: 30-40%, and total C4A3$: 50-60%, α H ′-C2S: 35~45%, β-C2S: <5%, C4AF: <10%, and the rest are mixed transition phases.
[0010] The present invention provides a method for preparing the high-belite ferroaluminate cement clinker described in the above scheme, comprising the following steps:
[0011] The high-belite ferroaluminate cement raw material powder is mixed with water and pressed into a shape to obtain a raw material cake;
[0012] The raw cake is subjected to a first heating, a first calcination, a second heating and a second calcination in sequence, and the obtained raw cake is placed in air and rapidly cooled to room temperature to obtain the high-belite alumina-ferrocement clinker.
[0013] Preferably, the temperature of the first calcination is 900° C., and the holding time is 0.5 to 1 h.
[0014] Preferably, the temperature of the second calcination is 1250-1350° C., and the holding time is 0.5-1 h.
[0015] Preferably, the mass ratio of the high-belite alumina ferroaluminate cement raw material powder to water is 1:0.1-0.15.
[0016] Preferably, the first heating rate is 10°C / min; and the second heating rate is 5°C / min.
[0017] Preferably, the particle size of the high-belite alumina ferroaluminate cement raw material powder is below 75 μm.
[0018] Preferably, the pressing pressure is 20 to 25 tons.
[0019] The present invention provides a cement comprising high-belite ferroaluminate cement clinker and anhydrite. The high-belite ferroaluminate cement clinker is the high-belite ferroaluminate cement clinker described in the above scheme or the high-belite ferroaluminate cement clinker prepared by the preparation method described in the above scheme.
[0020] The present invention provides a high-belite ferroaluminate cement raw material, which, in terms of mass percentage, has a chemical composition of: CaCO3: 50-60%, SiO2: 10-13%, Al2O3: 15-20%, Fe2O3: 3-5%, CaSO4: 5-10%, B2O3: 1-1.5%, BaCO3: 5-8%, and CuO: 0-0.5%. The present invention introduces B element into the raw material, which can transform the C2S crystal form in the clinker after firing from β-C2S to α-C2S with higher hydration activity. H ′-C2S, effectively improving the late strength development of the high-belite ferroaluminate cement system; by introducing the Ba element into the raw material, the C4A3$ crystal form in the clinker after firing can be partially transformed from the orthorhombic crystal form to the cubic crystal form, effectively alleviating the early hydration and hardening rate of the high-belite ferroaluminate cement system; by introducing the Cu element into the cement raw materials, the temperature of the molten phase during the clinker firing process can be effectively reduced, high-temperature solid-phase reaction can be promoted, and the firing temperature of cement clinker can be effectively reduced. The present invention effectively changes the crystal structure of the main mineral phase in the cement clinker by introducing the composite activated ions, so that it has higher mechanical strength after being mixed with seawater and solidified. DETAILED DESCRIPTION
[0021] The invention provides a high-belite ferroaluminate cement raw material, which comprises, by weight percentage, the following chemical compositions: CaCO3: 50-60%, SiO2: 10-13%, Al2O3: 15-20%, Fe2O3: 3-5%, CaSO4: 5-10%, B2O3: 1-1.5%, BaCO3: 5-8% and CuO: 0-0.5%.
[0022] The chemical composition of the raw material of the high-belite ferroaluminate cement provided by the present invention includes 50-60% of CaCO3 in terms of mass percentage; in a specific embodiment, it can be 50%, 52%, 54%, 56%, 58% or 60%. In the present invention, the role of the CaCO3 is to provide the Ca element required for clinker burning.
[0023] The chemical composition of the raw material of the high-belite ferroaluminate cement provided by the present invention includes SiO2 10-13% by weight, and in a specific embodiment, it can be 10%, 11%, 12% or 13%. In the present invention, the role of the SiO2 is to provide the Si element required for the clinker burning.
[0024] The chemical composition of the raw material of the high-belite alumina-ferrocement provided by the present invention includes 15-20% Al2O3 by weight percentage; in a specific embodiment, it can be 15%, 16%, 17%, 18%, 19% or 20%. In the present invention, the role of the Al2O3 is to provide the Al element required for clinker burning.
[0025] The chemical composition of the raw material of the high-belite ferroaluminate cement provided by the present invention includes 3-5% Fe2O3 by weight percentage; in a specific embodiment, it can be 3%, 3.5%, 4%, 4.5% or 5%. In the present invention, the role of the Fe2O3 is to provide the Fe element required for clinker burning.
[0026] The chemical composition of the raw material of the high-belite ferroaluminate cement provided by the present invention includes 5-10% CaSO4 in terms of mass percentage; in a specific embodiment, it can be 5%, 6%, 7%, 8%, 9% or 10%. In the present invention, the role of the CaSO4 is to provide the Ca and S elements required for the clinker burning.
[0027] The chemical composition of the raw material of the high-belite alumina ferrocement provided by the present invention includes B2O3 1-1.5% by weight; in a specific embodiment, it can be 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%. The present invention introduces the B element into the raw material, which can transform the C2S crystal form in the clinker after burning from β-C2S to α-C2S with higher hydration activity. H ′-C2S, effectively improves the later strength development of high-belite ferroaluminate cement system.
[0028] The chemical composition of the raw material of the high-belite aluminoaluminate cement provided by the present invention includes BaCO35-8% by weight; in a specific embodiment, it can be 5%, 6%, 7% or 8%. By introducing the Ba element into the raw material, the present invention can partially transform the C4A3$ crystal form in the clinker from the orthorhombic crystal form to the cubic crystal form after firing, effectively alleviating the early hydration and hardening rate of the high-belite aluminoaluminate cement system.
[0029] The chemical composition of the high-belite ferroaluminate cement raw material provided by the present invention includes 0-0.5% CuO in terms of mass percentage, and in a specific embodiment, it can be 0%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. The present invention can effectively reduce the temperature of the molten phase during the clinker burning process by introducing the Cu element into the cement raw material, promote high-temperature solid phase reaction, and effectively reduce the cement clinker burning temperature.
[0030] The present invention does not make any special requirements on the specific raw materials corresponding to the high-belite alumina ferroaluminate cement raw material, as long as the above chemical composition is met.
[0031] The present invention effectively changes the crystal structure of the main mineral phase in the cement clinker by introducing the composite activated ions, so that the cement clinker has higher mechanical strength after being mixed with seawater, coagulated and hardened.
[0032] The present invention provides a high-belite ferroaluminate cement clinker, which is obtained by calcining the high-belite ferroaluminate cement raw material;
[0033] Based on the mass percentage of 100%, the mineral phase composition of the high-belite ferroaluminate cement clinker includes: orthorhombic C4A3$: 20-30%, cubic C4A3$: 30-40%, and total C4A3$: 50-60%, α H ′-C2S: 35~45%, β-C2S: <5%, C4AF: <10%, and the rest are mixed transition phases.
[0034] In a specific embodiment, the content of rhombic C4A3$ in the high-belite ferroaluminate cement clinker can be 20%, 22%, 24%, 26%, 28% or 30%, and the content of cubic C4A3$ can be 30%, 32%, 34%, 36%, 38% or 40%, α H The content of '-C2S may be 35%, 37%, 39%, 40%, 42%, 43% or 45%.
[0035] The present invention has no particular limitation on the type of the mixed transition phase, which may be C 12 A7, C2AS, CA, CA2. In the present invention, the mixed transition phase is a product other than the target, and the lower the content, the better.
[0036] In the present invention, the high belite alumina ferrocement clinker contains a large amount of α H ′-C2S phase, α H Compared with β-C2S, ′-C2S has higher hydration activity and can effectively improve the later strength development of high-belite ferroaluminate cement system.
[0037] In addition, the high-belite ferroaluminate cement clinker also contains a large amount of cubic C4A3$ phase, which effectively alleviates the early hydration and hardening rate of the high-belite ferroaluminate cement system.
[0038] The present invention provides a method for preparing the high-belite ferroaluminate cement clinker described in the above scheme, characterized in that it comprises the following steps:
[0039] The high-belite ferroaluminate cement raw material powder is mixed with water and pressed into a shape to obtain a raw material cake;
[0040] The raw cake is subjected to a first heating, a first calcination, a second heating and a second calcination in sequence, and the obtained raw cake is placed in air and rapidly cooled to room temperature to obtain the high-belite alumina-ferrocement clinker.
[0041] The invention prepares raw material cakes by mixing high-belite ferroaluminate cement raw material powder with water and pressing the mixture into shapes.
[0042] In the present invention, the preparation of the high-belite ferroaluminate cement raw meal powder preferably includes: drying the raw materials corresponding to the high-belite ferroaluminate cement raw meal respectively, weighing each raw material in proportion, premixing them in a ball mill, and then mixing them in a mixer to obtain the high-belite ferroaluminate cement raw meal powder.
[0043] In the present invention, the drying temperature is preferably 105°C and the drying time is preferably 24 hours; the present invention has no special requirements for the premixing and mixing time, and uniform mixing is sufficient. In the present invention, the particle size of the high-belite ferroaluminate cement raw material powder is preferably below 75 μm.
[0044] In the present invention, the mass ratio of the high-belite alumina ferroaluminate cement raw material powder to water is 1:0.1-0.15; in a specific embodiment, it can be 1:0.1, 1:0.13 or 1:0.15.
[0045] In the present invention, the compression molding is preferably carried out in a tablet press; the compression molding pressure is preferably 20 to 25 tons, and in specific embodiments, it can be 20 tons, 21 tons, 22 tons, 23 tons, 24 tons or 25 tons. The present invention has no special requirements on the size of the raw material cake. In an embodiment of the present invention, the diameter of the raw material cake is preferably 40 mm. The present invention increases the contact area between the powders of each component by pressing into a cake, which facilitates the occurrence of chemical synthesis reactions during the clinker firing process and facilitates the firing of the clinker mineral phase.
[0046] The raw cake obtained after the compression molding is a wet cake, and the present invention preferably dries it to obtain a dry raw cake for subsequent sintering steps.
[0047] In the present invention, the drying temperature is preferably 105° C. and the drying time is preferably 24 hours.
[0048] After obtaining the raw cake, the present invention preferably sequentially performs a first heating, a first calcination, a second heating and a second calcination on the raw cake, and the obtained raw cake is placed in air and rapidly cooled to room temperature to obtain the high-belite ferroaluminate cement clinker.
[0049] In the present invention, the first heating rate is preferably 10°C / min; the first calcination temperature is preferably 900°C, and the holding time is preferably 0.5 to 1 hour. The present invention achieves the purpose of decarbonizing the raw materials through the first calcination.
[0050] In the present invention, the second heating rate is preferably 5°C / min; the second calcination temperature is preferably 1250-1350°C, and the holding time is preferably 0.5-1h. In a specific embodiment, the second calcination temperature can be 1250°C, 1300°C or 1350°C. The present invention promotes chemical reactions of various components to form various mineral phases through the second calcination.
[0051] In the present invention, the first calcination and the second calcination are preferably performed under an air atmosphere.
[0052] After the second calcination is completed, the present invention immediately places the obtained cake in air and rapidly cools it to room temperature. In the present invention, it is preferred to use a fan to rapidly cool the cake to room temperature.
[0053] The invention plays a role of stabilizing the high-temperature crystal form by rapid cooling in air.
[0054] After cooling to room temperature, the present invention preferably further comprises crushing and ball milling the obtained cake. In the present invention, the particle size of the high-belite alumina-ferrocement clinker is preferably below 75 μm.
[0055] The present invention provides a cement comprising the above-mentioned high-belite ferroaluminate cement clinker and anhydrite. In the present invention, the mass ratio of the high-belite ferroaluminate cement clinker to the anhydrite is preferably 95:5.
[0056] The present invention has no special requirements for the preparation of the cement, and the high-belite alumina-ferrocement clinker and anhydrite are directly mixed and then ball-milled.
[0057] The following is a detailed description of the high-belite ferroaluminate cement raw material, clinker and the preparation methods of cement and clinker provided by the present invention in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0058] Examples 1-2 and Comparative Examples 1-2
[0059] The raw material ratio is shown in Table 1:
[0060] Table 1 Raw material composition of the embodiments and comparative examples (mass percentage, %)
[0061] raw materials <![CDATA[CaCO3]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[CaSO4]]> <![CDATA[B2O3]]> <![CDATA[BaCO3]]> CuO Example 1 52.66 10.28 17.75 3.87 7.10 1.19 7.15 0.00 Example 2 52.50 10.25 17.70 3.86 7.08 1.19 7.13 0.29 Comparative Example 1 57.45 11.21 19.37 4.23 7.75 0.00 0.00 0.00 Comparative Example 2 56.71 11.07 19.12 4.17 7.65 1.28 0.00 0.00
[0062] Note: Compared with Comparative Example 1, Example 1, Example 2 and Comparative Example 2 contain activated ions (i.e., B2O3, BaCO3, CuO), and the other components are consistent with Comparative Example 1 after normalization.
[0063] The required raw materials were dried in a drying oven at a constant temperature of 105°C for 24 hours, and 1 kg of the required raw materials were weighed according to the mass percentage in the above table. The weighed raw materials were ball-milled to a particle size of less than 200 mesh, and the mixed powders obtained after ball milling were uniformly mixed with a mixer for 24 hours to obtain raw material powder.
[0064] The raw material powder and deionized water are uniformly mixed in a mass ratio of 1:0.15, and pressed into a raw material cake with a diameter of 40 mm using a tablet press at a pressure of 20 tons. The raw material cake is dried at a constant temperature of 105°C in a drying oven for 24 hours and cooled to room temperature, then placed in a muffle furnace and heated to 900°C at a heating rate of 10°C / min, and kept warm for 0.5 hours, and then continued to heat to 1300°C at a heating rate of 5°C / min, and kept warm for 1 hour. After calcination, the clinker cake is taken out of the furnace at 1300°C, and the clinker cake is quickly cooled to room temperature in the air using a fan. The cooled clinker cake is crushed and ball-milled to less than 200 mesh to obtain high-belite ferroaluminate cement clinker. The mineral composition of the cement clinker of each embodiment and comparative example is shown in Table 2.
[0065] Table 2 Mineral phase composition of the embodiments and comparative examples (mass percentage, %)
[0066]
[0067]
[0068] Note: In Table 2, Examples 1 to 2 also contain trace amounts of mixed transition phases that are not listed, and therefore, are less than 100%; Comparative Example 2 is rounded off when retaining one decimal point, resulting in a total amount of mineral phases of 100.1%, which is hereby explained.
[0069] The high-belite aluminoaluminate cement clinker of the embodiment and the comparative example was mixed with anhydrite at a mass ratio of 95:5, and after premixing, the mixture was ball-milled in a ball mill until the powder particle size was less than 200 meshes to obtain high-belite aluminoaluminate cement.
[0070] The prepared high belite aluminaluminoaluminate cement was cast into a cubic specimen with a side length of 25 mm according to a water-cement ratio of 0.3. The mixing water was artificially prepared seawater and tap water (fresh water), respectively. After curing in artificially prepared seawater and tap water to the specified age, the compressive strength was tested according to the "Cement Mortar Strength Test Method" GB / T17671-1999. The proportions of each component of artificially prepared seawater refer to the specification ASTM D1141-98. The pore solution of the specimen at the age of 28 days was squeezed by the method of squeezing concrete pore solution, and the pH value of the pore solution was tested using a pH meter. The compressive strength of the specimen and the pore solution test results are shown in Table 3.
[0071] Table 3 Performance data of embodiments and comparative examples
[0072]
[0073] Comparing the compressive strength of Comparative Example 1 (without adding activating ions) and Comparative Example 2 (solely adding B2O3 activating ions) with the compressive strength of Examples 1-2 (adding B2O3: 1-1.5%, BaCO3: 5-8%, CuO: 0-0.5% to the raw materials of high-belite ferroaluminate cement clinker), it is found that under the condition of similar cement clinker particle size composition, the high-belite ferroaluminate cement clinker modified by composite ion addition has better early compressive strength and mid-to-late compressive strength after seawater mixing and curing, breaking through the limitation of slow development of mid-to-late compressive strength. The compressive strength of Comparative Example 2 after seawater mixing and curing with single B2O3 is lower than that of the freshwater specimen, and is suitable for freshwater mixing and curing specimens. Compared with Comparative Examples 1 and 2, Example 2 has similar 28-day compressive strength after seawater mixing, but has higher 3-day and 7-day compressive strength, has early strength characteristics, and the seawater mixing specimen has higher compressive strength than the freshwater mixing specimen. In addition, after the composite-ion-modified high-belite ferroaluminate cement clinker was mixed with seawater and cured for 28 days, the pH value of the solution in the specimen pores had the characteristics of low alkalinity (pH value <13), which was friendly to the durability of FRP bars and was suitable for FRP bar-reinforced seawater and sea sand concrete structures.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-belite ferroaluminate cement raw material, characterized in that: The chemical composition, in terms of mass percentage, includes: CaCO3: 50-60%, SiO2: 10-13%, Al2O3: 15-20%, Fe2O3: 3-5%, CaSO4: 5-10%, B2O3: 1-1.5%, BaCO3: 5-8%, and CuO: 0-0.5%.
2. A high-belite ferroaluminate cement clinker, characterized in that: Obtained by calcining the high-belite alumina-ferrocement raw material described in claim 1; Based on the mass percentage of 100%, the mineral phase composition of the high-belite ferroaluminate cement clinker includes: orthorhombic C4A3$: 20-30%, cubic C4A3$: 30-40%, and total C4A3$: 50-60%, α H ′-C2S: 35~45%, β-C2S: <5%, C4AF: <10%, and the rest are mixed transition phases.
3. The method for preparing high-belite ferroaluminate cement clinker according to claim 2, characterized in that: The following steps are involved: The high-belite ferroaluminate cement raw material powder is mixed with water and pressed into a shape to obtain a raw material cake; The raw cake is subjected to a first heating, a first calcination, a second heating and a second calcination in sequence, and the obtained raw cake is placed in air and rapidly cooled to room temperature to obtain the high-belite ferroaluminate cement clinker.
4. The preparation method according to claim 3, characterized in that: The temperature of the first calcination is 900° C., and the holding time is 0.5 to 1 hour.
5. The preparation method according to claim 3 or 4, characterized in that: The temperature of the second calcination is 1250-1350° C., and the holding time is 0.5-1 h.
6. The preparation method according to claim 3, characterized in that: The mass ratio of the high-belite alumina ferroaluminate cement raw material powder to water is 1:0.1-0.
15.
7. The preparation method according to claim 3 or 4, characterized in that: The first heating rate is 10°C / min; the second heating rate is 5°C / min.
8. The preparation method according to claim 3, characterized in that: The particle size of the high-belite ferroaluminate cement raw material powder is below 75 μm.
9. The preparation method according to claim 3, characterized in that: The pressure of the pressing molding is 20 to 25 tons.
10. A cement, characterized in that: The invention comprises high-belite ferroaluminate cement clinker and anhydrite, wherein the high-belite ferroaluminate cement clinker is the high-belite ferroaluminate cement clinker according to claim 2 or the high-belite ferroaluminate cement clinker prepared by the preparation method according to any one of claims 3 to 9.